Conflict Resolution Strategies and Sustainable Employees’ Morale - Bello, Bashiru Akande; Okafor, Linus Izeduino; Onifade, Temitayo Alice; Opele, Adedayo Mathias; Patrick, Ologbenla; Lawal, Oloyede Raheem; Hamzat, Bolaji Saheed; Afolayan, Michael Ayorinde; Osifeso, Oluwaseun Omolola; Nnoli, Ikenna Theodore (International Review of Management and Marketing, 2026)
This study investigated the impact of Conflict Resolution Strategies on Sustainable Employees’ Morale in Beverage Companies in Agbara Industrial Estate, Ogun State, Nigeria. The objective of the study was to examine the impact of alternative conflict resolution strategies (competition, collaboration, accommodation, compromising strategies) on Sustainable Employees’ Morale in selected Beverages Companies. Four beverage companies were selected and a descriptive survey research design was used to establish the association between conflict resolution strategies and sustainable employees’ morale. The population for the study was 2,830, which comprised Managers, Senior Staff and Junior Staff of the four selected beverage companies in Agbara Industrial Estate, Ogun State, Nigeria. A sample size of 350 respondents was selected through Taro Yamane's sample size determination formula. Primary data was employed in collecting information from respondents through a well-structured questionnaire. Results of the study revealed that conflict resolution strategies had a significant impact on sustainable employees’ morale in the Beverage Companies. Collaborating and competing strategies were found to have a positive relationship with employee morale, while accommodating strategy was found to have a negative relationship with employees’ morale. Compromising strategy was found not to be associated with significant differences in employees’ morale levels. The study therefore, recommends that companies should focus on implementing collaborating and competing strategies to improve employees’ morale to ensure a more productive and positive work environment.